2008
DOI: 10.1016/j.biopsych.2008.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Estriol Levels in Women with and Without Prenatal Antidepressant Treatment

Abstract: Objective-Prenatal antidepressant use has been associated with shorter pregnancy duration and an increased risk for preterm birth. This study measured saliva levels of estriol, a hormone which increases exponentially in the few weeks before spontaneous labor, in pregnant women with and without antidepressant treatment.Method-Saliva estriol levels were obtained across the day at three time points during pregnancy in 77 subjects with either a history of DSM-IV major depressive disorder (MDD) who were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Studies have shown that SSRIs readily cross the placenta (Hendrick et al, 2003), are present in amniotic fluid (Loughhead et al, 2006) and newborns may experience withdrawal like symptoms after birth (Moses-Kolko et al, 2005). Suri and colleagues (2008) noted higher estriol levels in the latter part of pregnancy among women using anti-depressants, and this may indicate increased/accelerated fetal production of estriol precursors. SSRIs can also lower serotonin levels in platelets which, in some studies have shown clinical evidence of compromised coagulation and predisposition to hemorrhage (Looper, 2007).…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…Studies have shown that SSRIs readily cross the placenta (Hendrick et al, 2003), are present in amniotic fluid (Loughhead et al, 2006) and newborns may experience withdrawal like symptoms after birth (Moses-Kolko et al, 2005). Suri and colleagues (2008) noted higher estriol levels in the latter part of pregnancy among women using anti-depressants, and this may indicate increased/accelerated fetal production of estriol precursors. SSRIs can also lower serotonin levels in platelets which, in some studies have shown clinical evidence of compromised coagulation and predisposition to hemorrhage (Looper, 2007).…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…Moreover, the use of SSRIs alters the 5-TH levels increased risk of intrauterine growth retardation and preterm delivery by impairing placental blood flow [15]. It is also reported that women using antidepressants had higher saliva estriol levels compared to non-users [16] and elevated levels of estriol have been associated with preterm birth [17]. Secondly, antidepressant medication are prescribed to treat depression so that the observed associations could be explained by the residual depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts encompassed gene expression profiling of peripheral mononuclear cells (1, 2), biochemical evaluations of serum (3), urine (4), saliva (5), and cerebrospinal fluid (6), gene association studies of DNA markers (7) and many other approaches. More recently, inducible pluripotent stem cells (IPSCs) emerged as a very promising model for studying neuronal lineage disturbances across various disorders (810).…”
Section: Introductionmentioning
confidence: 99%